2020
DOI: 10.3390/nu12061825
|View full text |Cite
|
Sign up to set email alerts
|

Skin Carotenoid Level as an Alternative Marker of Serum Total Carotenoid Concentration and Vegetable Intake Correlates with Biomarkers of Circulatory Diseases and Metabolic Syndrome

Abstract: To confirm the usefulness of noninvasive measurements of skin carotenoids to indicate vegetable intake and to elucidate relationships between skin carotenoid levels and biomarkers of circulatory diseases and metabolic syndrome, we conducted a cross-sectional study on a resident-based health checkup (n = 811; 58% women; 49.5 ± 15.1 years). Skin and serum carotenoid levels were measured via reflectance spectroscopy and high-performance liquid chromatography, respectively. Vegetable intake was estimated using a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 44 publications
7
19
1
Order By: Relevance
“…A relationship between blood carotenoid levels and vegetable intake was also reported by Campbell et al using a frequency survey Food Frequency Questionnaire [ 16 ]. These previous studies are consistent with ours, suggesting that serum carotenoid concentrations could be an indicator of vegetable intake and that this could be expected to be helpful for nutritional guidance according to which non-invasive measurement of skin carotenoid levels has begun to be implemented [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…A relationship between blood carotenoid levels and vegetable intake was also reported by Campbell et al using a frequency survey Food Frequency Questionnaire [ 16 ]. These previous studies are consistent with ours, suggesting that serum carotenoid concentrations could be an indicator of vegetable intake and that this could be expected to be helpful for nutritional guidance according to which non-invasive measurement of skin carotenoid levels has begun to be implemented [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…A cross-sectional study in a group of ethnically diverse adults in New Zealand found an inverse correlation between skin carotenoid concentrations and BMI ( 54 ). This correlation was confirmed in a sample of Japanese adults ( 55 ). Few studies have examined this association in pediatric populations.…”
Section: Discussionmentioning
confidence: 53%
“…Of the carotenoids present in the skin, β-carotene was present in the highest concentration (0.517 µg/mL). Those authors found that the levels of carotenoids in the skin were associated with a lower body mass index, blood pressure, index of insulin resistance, and triglyceride concentration, as well as an increase in HDL-c levels [ 69 ].…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%